Peran Relawan Demokrasi (Relasi) Dalam Meningkatkan Partisipasi Pemilih Pada Pemilu 2019 di Provinsi Jambi - Mochammad Farisi; Rio Yusri Maulana (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2020)
The volunteer democracy program is a social movement intended to increase voter participation and quality in exercising their voting rights. This program involves the widest possible participation of the community where they are placed as pioneers of democracy for their communities. Democracy volunteers become KPU partners in carrying out the agenda of outreach and voter education based in districts/cities. This form of community participation is expected to be able to encourage the growth of high awareness and full responsibility of the community to use their rights in elections optimally. The Democracy Volunteer Program initiated by the KPU involved community groups from 11 (eleven) strategic voter bases, namely; family base, novice voter base, young voter base, women voter base, disabled people base, special needs voter base, marginal people base, community base, religious base, internet citizen base, and democratic volunteer base. Relationships will be formed on each basis which will then become extension agents in each community. The Relationship Program is motivated by the level of voter participation which tends to decline, the last four national elections and the implementation of post-conflict local elections in various regions show that indication, namely the 1999 election (93%), the 2004 election ( 84.1%), the 2009 election (70.9%), 2014 election (75.11%). The trend of decreasing participation is a challenge for the KPU on how to increase participation in the 2019 Election, for this reason, this article explains what the factors are causing the decline in voter participation and how the Relation strategy is to increase voter participation in the 2019 Election in Jambi